Related factor analysis of anemia in patients with type 2 diabetic kidney disease - Zhang Jing; Chen Guang-mei; Fan Wen-xing; Su Feng (Linchuang shenzangbing zazhi)
Objective To explore the related factors of anemia in patients with type 2 diabetic kidney disease（DKD）.Methods In this retrospective study, 334 patients with a clinical diagnosis of type 2 DKD were recruited and divided into anemia and non-anemia groups.The relationships of anemia with clinical manifestations and laboratory findings were analyzed.Binary Logistic regression analysis was performed for evaluating the related factors in type 2 DKD patients of different genders.Results Significant inter-group differences existed in complement（C4）,serum creatinine（Scr）,cystatin C（CysC）,retinol binding protein（RBP）,ferritin（SF）,urinary albumin/creatinine（UACR）,diabetes duration, body mass index（BMI）,hemoglobin（Hb）,glycosylated hemoglobin（HbA1 c）,complement（C3）,albumin（Alb）,indirect bilirubin（IDBIL）,estimated ball filtration rate（eGFR）,cholesterol（TC）,iron（Fe）and calcium（Ca）for males（P<0.05）;for females, Scr, CysC,RBP,UACR,Hb, Alb, Fe, IDBIL,eGFR,C3 and Ca were significantly different between two groups（P<0.05）.Logistic regression analysis showed that BMI,eGFR and Alb were associated with anemia in males（P<0.05）;BMI,eGFR and Ca were correlated with anemia in females（P<0.05）.Conclusions Anemia in type 2 diabetic kidney disease patients is closely correlated with deterioration of renal function, disorder of iron metabolism, hypocalcemia, malnutrition and microinflammation.